From the suburb to the steppe: the city, modernity and nature in poetry and narrative of the Group of 27 - Ramírez Guerrero, Ángela (2022)
This article is about the exaltation of the city and modernity and the return to nature in a selection of writers of the Group of 27. The objectives of this work include the analysis of each of the texts separately and, subsequently, make a comparison between the authors with the theme of the city and modernity and the authors who exalt nature. The selected corpus is a poem and in the story of each writer: Concha Méndez, Lucía Sánchez, Benjamín Jarnés, Cristina de Arteaga, Margarita Ferreras, Josefina Romo and Max Aub. The findings suggest strong contrasts between writers who return to nature in his literary production, but not so in the authors that work with the theme of the city and modernity.